2009
DOI: 10.1029/2008jb005808
|View full text |Cite
|
Sign up to set email alerts
|

Geoid and gravity anomaly data of conjugate regions of Bay of Bengal and Enderby Basin: New constraints on breakup and early spreading history between India and Antarctica

Abstract: [1] Timing of breakup of the Indian continent from eastern Gondwanaland and evolution of the lithosphere in the Bay of Bengal still remain as ambiguous issues. Geoid and free-air gravity data of Bay of Bengal and Enderby Basin are integrated with shipborne geophysical data to investigate the early evolution of the eastern Indian Ocean. Geoid and gravity data of the Bay of Bengal reveal five N36°W fracture zones (FZs) and five isolated NE-SW structural rises between the Eastern Continental Margin of India (ECMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 78 publications
5
50
1
Order By: Relevance
“…Furthermore, due to the requirement of accommodating the Elan Bank microcontinent in the breakup scenario, Gaina et al (2003) proposed a two-stage breakup history for the Eastern Continental Margin of India (ECMI): first, the India-Antarctica separation during M9o-M2o; second, the separation of Elan Bank from the present-day ECMI at M2. Recent geophysical studies along the ECMI are in agreement with the above doublebreakup scenario (Krishna et al 2009;Radhakrishna et al 2012). Based on the basement trends in the multichannel seismic reflection data, Radhakrishna et al (2012) identified several NW-SE-oriented fracture zones in the BOB, and these are in accordance with the earliest seafloor spreading direction.…”
Section: Regional Geotectonic History Of the Bobsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, due to the requirement of accommodating the Elan Bank microcontinent in the breakup scenario, Gaina et al (2003) proposed a two-stage breakup history for the Eastern Continental Margin of India (ECMI): first, the India-Antarctica separation during M9o-M2o; second, the separation of Elan Bank from the present-day ECMI at M2. Recent geophysical studies along the ECMI are in agreement with the above doublebreakup scenario (Krishna et al 2009;Radhakrishna et al 2012). Based on the basement trends in the multichannel seismic reflection data, Radhakrishna et al (2012) identified several NW-SE-oriented fracture zones in the BOB, and these are in accordance with the earliest seafloor spreading direction.…”
Section: Regional Geotectonic History Of the Bobsupporting
confidence: 58%
“…1). The oceanic lithosphere in the BOB region evolved during the breakup of India and Antarctica in the Early Cretaceous period (Powell et al 1988) followed by three major phases of seafloor spreading: the initial NW-SE spreading up to the Mid-Cretaceous period, the N-S spreading until the early Tertiary and the present NE-SW spreading (Curray et al 1982;Krishna et al 2009). Royer and Sandwell (1989) observed that most of the BOB oceanic crust was formed during the above first two phases.…”
Section: Regional Geotectonic History Of the Bobmentioning
confidence: 99%
“…The first breakup occurred with separation of Greater India from Australia and East Antarctica during the Early Cretaceous Royer and Coffin 1992;Gopala Rao et al 1997;Müller et al 2000). In the second stage the Elan Bank, a submerged microcontinent lies presently on the western margin of the Kerguelen Plateau in the southern Indian Ocean, broke up from the present-day eastern margin of India at about 120 Ma (Gaina et al 2003(Gaina et al , 2007Borissova et al 2003;Krishna et al 2009). The breakup sequences and their timings suggest that most part of the oceanic crust in the Bay of Bengal was evolved during the Cretaceous Magnetic Quiet Period (120-83 Ma).…”
Section: Tectonic Settingmentioning
confidence: 99%
“…1); the presence of thick sediments and lack of identifiable magnetic anomalies in the northern part of BOB prevents the recognition of NW-SE spreading regime identified elsewhere (e.g. Krishna et al, 2009). Recently, based on basement trends observed from large number of multi-channel reflection profiles, Radhakrishna et al (2012) have mapped several NW-SE trending fracture zones in the northern part of the BOB.…”
Section: Regional Geologic Setting and Evolutionmentioning
confidence: 99%